1990
DOI: 10.1148/radiology.175.1.2315468
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy: initial experience with Tc-99m HMPAO SPECT of the brain.

Abstract: The outlook for children with cerebral palsy is determined by the severity of motor problems and the presence of associated disabilities, in which early detection remains a medical challenge. The authors studied 13 children (aged 13 months to 12 years) with cerebral palsy by means of single photon emission computed tomography (SPECT) of the brain with technetium-99m hexamethylpropyleneamineoxime (HMPAO). In all children with hemiplegia, SPECT demonstrated hypoperfusion in the hemisphere contralateral to the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…We also found perfusion defects after normal cranial US in infants with later CP. Furthermore, as earlier has been demonstrated, also the SPET may be normal as in 2 cases of this study in infants with mild CP [1,21]. There may be sometimes diffuse white matter lesions with no extensions to the cortical layers or to the basal ganglias.…”
Section: Discussionsupporting
confidence: 73%
“…We also found perfusion defects after normal cranial US in infants with later CP. Furthermore, as earlier has been demonstrated, also the SPET may be normal as in 2 cases of this study in infants with mild CP [1,21]. There may be sometimes diffuse white matter lesions with no extensions to the cortical layers or to the basal ganglias.…”
Section: Discussionsupporting
confidence: 73%
“…Early landmarks in SPECT research were made by studies that reported findings on patient groups without reference to a control group [Abdul-Dayem et al, 1987;Ryding et al, 1988;Shen et al, 1990;Denays et al, 1990;Holman et al, 1991;Tumeh et al, 1990;Berman et al, 1987]. Other seminal studies used controls without reference to gender or age [Costa et al, 1988;Holman et al, 1991], or they compared patient groups to one another.…”
Section: Methodsmentioning
confidence: 99%
“…SPECT has been used in cases of epilepsy, head injuries, cerebral palsy, dementias, drug use, depression, schizophrenia, obsessive-compulsive disorders, and eating disorders [Ryding et al, 1988;Shen et al 1990;AbdelDayem et al, 1987;Denays, 1990;Johnson et al, 1993;Costa et al, 1988;Gemmell et al 1987;Holman et al, 1991;Tumeh et al, 1990;Mathew et al, 1980;Ariel et al, 1983;Berman et al, 1987;Stephenson, 1990]. SPECT has been found to be more sensitive than TCT in diagnostic work with human immunodeficiency virus (HIV) encephalopathy [Masdeu et al, 1991;LaFrance et al, 1988] and acute head lesions [Abdel-Dayem et al, 1987].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the wide range of neural regions examined across studies, and the likelihood of etiological heterogeneity in the SLI populations across these studies, there appears to be consistent evidence that SLI is strongly associated with abnormalities of at least two structures: frontal cortex and the basal ganglia. To our knowledge, every study that has explicitly examined frontal regions has reported frontal abnormalities (Clark and Plante, 1998a; Cohen et al, 1989;Denays et al, 1989;Gallagher and Watkin, 1997;Gauger et al, 1997;Jernigan et al, 1991; Kabani et al, 1997) (KE family: Liegeois et al, 2002;. This seems to hold especially for inferior frontal regions (Clark and Plante, 1998a; Cohen et al, 1989;Gauger et al, 1997;Jernigan et al, 1991;Lou et al, 1984) (KE family: Liegeois et al, 2002;, in particular for Broca's area (Gauger et al, 1997;Lou et al, 1984) (KE family: Liegeois et al, 2002;.…”
Section: Studies Of the Neural Correlates Of Sli Anatomical Studiesmentioning
confidence: 99%
“…It might also explain changes in the amount of gray matter or in the gray matter density in this region (Belton et al, 2002;Watkins et al, 2002). However, these and other types of abnormalities in these regions, such as hypoperfusion (Denays et al, 1989;Lou et al, 1984), or changes in the level of functional activity (Liegeois et al, 2003;, are quite difficult to interpret, and future research is clearly needed to examine this issue.…”
Section: Insert Table Around Herementioning
confidence: 99%